REFORMASI PENDIDIKAN CELESTIAL: STUDI PEMIKIRAN KHALIFAH DARI HASAN LANGGULUNG - Rosyid, Abdul (STAI Darul Qalam Tangerang, 2021)
This research was intended to explain the caliph's education reforms initiated by Islamic education expert, Hasan Langgulung. Caliph's Education Reform is a spiritual-based education or can also be called heaven education, pendidikan Divine based on guidance wahyu Allah. This educational concept seeks to develop the education of faith, righteousness, faithfulness, intelligence and character who have the skills and desire to continue learning and serving others throughout their lives. This research is qualitative research that focuses on research in library research. This research uses two approaches, namely philosophical approach and scientific approach. Integrating a philosophical approach with a scientific approach is intended to find answers to educational problems in an effort to design concepts. This paper shows that the paradigm of the caliph's education reform of Langgulung, aimed at exploring, growing and developing, as well as optimizing all human potential as caliphs on this earth, to realize their well-being, worldly and ukhrawi in their capacity as Servants of God.This research supports the opinion of educational experts such as David H. Yarn Jr., (2010), AN. Whitehead (1929), Syed Muhammad Naquib al-Attas (2014) who argued that,